Liver transplantation is a preferable alternative to palliative therapy for selected patients with advanced hepatocellular carcinoma - Aravinthan, Aloysious D.; Bruni, Silvio G.; Doyle, Adam C.; Thein, Hla-Hla; Goldaracena, Nicolas; Issachar, Assaf; Lilly, Leslie B.; Selzner, Nazia; Bhat, Mamatha; Sreeharsha, Boraiah; Selzner, Markus; Ghanekar, Anand; et al. (Springer, 2017)
Background: Patients with hepatocellular carcinoma (HCC) beyond the traditional criteria (advanced HCC) are typically offered palliation, which is associated with a 3-year survival rate lower than 30%. This study aimed to describe the outcomes for a subset of patients with advanced HCC who satisfied the Extended Toronto Criteria (ETC) and were listed for liver transplantation (LT). Materials & Methods: All patients listed in the Toronto liver transplant program with HCC beyond both the Milan and University of California, San Francisco criteria were included in this study. Data were extracted from the prospectively collected electronic database. All radiological images were reviewed by two independent radiologists. The primary endpoint was patient survival. Results: Between January 1999 and August 2014, 96 patients with advanced HCC were listed for LT, and 62 (65%) of these patients received bridging therapy while on the waiting list. Bridging therapy led to a significant reduction in tumor progression (p=0.02) and tumor burden (p <0.001). The majority of those listed underwent LT (n=69, 72%). Both tumor progression on waiting list (HR 4.973 [1.599 – 15.464], p=0.006) and peak AFP ≥400ng/ml (HR 4.604 [1.660 – 12.768], p=0.003) were independently associated with waiting list dropout. Post-LT HCC recurrence occurred in 35% (n=24). Among those with HCC recurrence, survival was significantly better for those who received curative treatment (p=0.004). The overall actuarial survival rates from the listing were 76% at 1 year, 56% at 3 years, and 47% at 5 years, and the corresponding rates from LT were 93%, 71%, and 66%. Conclusion: LT provides significantly better survival rates than palliation for patients with selected advanced HCC.